The Gender Equality Argument of Nasaruddin Umar - Neny Muthi'atul Awwaliyah (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
Nasarudin Umar is an Indonesian Muslim scholar who has concerns about the issue of gender relations. He contributes many reflective thoughts, including the book entitled Argumentasi Kesetaraan Gender Perspektif al-Qur'an (Gender equality argument from the perspective of Qur’an). This research is motivated by his intellectual anxiety toward Qur'anic texts that are often used as a tool of legitimacy and justification by patriarchalism. This notion has gender-biased and misogynous thought that places women as the secondactor in ritual and social contexts. In his research, Nasarudin assumes that gender inequality does not come from the character of religion, but it refers to the understanding of religious thought influenced by social construction. Also, he argues that there is still ambiguity of the Qur'an interpretation on whether gender is nature or dynamic nurture (social construction). To understand the authenticity of Qur'anic perspectives, Nasarudin researched the Qur'an verses that discuss male and female relationships by applying thematic analysis (called Tafsir Maudlui) with various approaches such as semantic-linguistic, normative-theological, and socio-historical. The result showed that the Qur'an does not expressly support the two gender paradigmsof either nature or nurture. It only accommodates certain elements within the two theories that are in line with the universal principles of Islam. Generally, the Qur'an recognizes the distinction between men and womenbut the distinction does not benefit one party while marginalizing the other. The distinction is needed precisely to support the harmonious, balanced, safe, full of virtue, and peaceful life.